Cancer Spectrum, Family History of Cancer and Overall Survival in Men with Germline BRCA1 or BRCA2 Mutations - Reichl, Florian; Muhr, Daniela; Rebhan, Katharina; Kramer, Gero; Shariat, Shahrokh F; Singer, Christian F; Tan, Yen Y (Journal of personalized medicine, 2021)
BACKGROUND: Men with germline BRCA1/2 mutations are not well studied compared to their female counterparts. This study evaluates the cancer characteristics, family history of cancer, and outcomes of male BRCA1/2 mutation carriers. METHODS: All men with germline BRCA1/2 mutations who attended genetic assessment between October 1995 and October 2019 at the Medical University of Vienna were identified. Clinicohistopathological features, family history of cancer, and outcomes were assessed by mutation status. RESULTS: Of the 323 men included, 45 (13.9%) had a primary cancer diagnosis, many of whom were BRCA2 carriers (75.5%). Breast cancer (BC) was the most common cancer (57.8%) followed by prostate cancer (15.6%). Invasive ductal carcinoma and hormone receptor positive tumors were the most common. Among 26 BC-affected patients, 42% did not have any relatives with cancer. Parent of origin was only known in half of the 26 men, with 42% of them inherited through the maternal lineage versus 8% through the paternal. BRCA2 carriers and those with a family history of BC had worse overall survival (20 y vs. 23 y BRCA1 carriers; P = 0.007; 19 y vs. 21 y for those without family history of BC; P = 0.036). CONCLUSION: Male BRCA2 carriers were most likely to develop cancer and had worse prognosis. In our dataset, BC was the most common cancer, likely due to referral bias. Not all mutation carriers present with BC or have a family history of cancer to warrant genetic testing.
Keywords: hereditary cancer; BRCA mutations; cancer spectrum; parent of origin; men; family history